Knowledge and orientations of medical interns toward periodontal disease in Saudi Arabia - Farah Asa'ad; Nassr Al-Maflehi; Bushra Alelyan; Lama Asaad; Walaa Alrumaih; Fatimah Alassad; Sara Alshakhs; Basma Alshakhs (Wolters Kluwer Medknow Publications, 2014)
Background and Aim: This study was conducted to assess the periodontal knowledge, orientations of Saudi medical interns and the medical curriculum. Study Population and Methodology: Questionnaires were distributed to 221 medical interns chosen randomly from two major educational institutions in Saudi Arabia. Questions were developed from literature reviews. The questionnaire had five true/false knowledge items, and eight Likert-scale questions. Data were analyzed by computerized SPSS (version 20). Level of significance was set at P < 0.05. Results: Of the 221 respondents, 66% were male and 34% were female. Most of the participants were 24 years old (48%). About 40% of the interns answered all five true/false general knowledge questions correctly, nearly half of the respondents (49.8%) reported they never asked patients if they were diagnosed with periodontal disease, 93.2% reported not receiving any training about periodontal disease in medical school, 23.5% reported they would feel absolutely uncomfortable performing a simple periodontal examination, about one-third of interns (29.4%) agreed that patients expect physicians to discuss/screen for periodontal disease, 43.9% felt that discussing/evaluating the periodontal status of their patients was peripheral to their role as physicians, nearly half of interns (48.4%) reported never screening patients for periodontal disease, and 33% stated they never referred patients to dentists. Conclusion: Medical interns were not prepared nor trained to screen patients for periodontal disease. They had limited knowledge about the association between periodontal health and general health. Oral health training as part of the medical curriculum is strongly recommended.